2020
DOI: 10.31234/osf.io/vzxw7
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Mindfulness Enhances Cognitive Functioning: A Meta-Analysis of 111 Randomized Controlled Trials

Abstract: Background: The past 30 years have witnessed growing scientific interest regarding the impact of mindfulness-based interventions (MBIs) on cognitive functions. Several theories propose that habitually exercising mindfulness skills can improve cognitive abilities, but no comprehensive quantitative reviews of the effect of MBIs on global and unique cognitive domains exist to date. Method: This systematic review thus examined the effects of MBI on global cognitive ability (GCA) and 16 specific cognitive domains. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…Moreover, the field could benefit from continuing to test EF indices as reliable predictors or markers of treatment response for depression and anxiety, as suggested by various studies (e.g., [129,130]). Relatedly, based on recent evidence, such efforts might be augmented by investigating if cognitive-behavioral therapies (CBTs) (e.g., behavioral activation, cognitive remediation, problem-solving therapy, personalized, environment-focused, and technology-facilitated CBTs) [131][132][133][134][135][136], mindfulness-based interventions [137], EF training [138], and pharmacological treatments [139], could simultaneously alleviate depression and enhance EF capacities.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the field could benefit from continuing to test EF indices as reliable predictors or markers of treatment response for depression and anxiety, as suggested by various studies (e.g., [129,130]). Relatedly, based on recent evidence, such efforts might be augmented by investigating if cognitive-behavioral therapies (CBTs) (e.g., behavioral activation, cognitive remediation, problem-solving therapy, personalized, environment-focused, and technology-facilitated CBTs) [131][132][133][134][135][136], mindfulness-based interventions [137], EF training [138], and pharmacological treatments [139], could simultaneously alleviate depression and enhance EF capacities.…”
Section: Discussionmentioning
confidence: 99%
“…Findings from systematic reviews and meta-analyses further corroborate this evidence, with support found for MBIs' ability to enhance positive mood, decrease symptoms of anxiety and depression, improve sleep quality and decrease chronic insomnia (Hazlett-Stevens et al, 2019). Additionally, meta-analytic and review findings indicate substantial support for the beneficial effects of MBIs on memory, and executive functioning, in particular, processing speed, sustained attention accuracy, and subjective attentional control (Chan et al, 2019;Hazlett-Stevens et al, 2019;Zainal & Newman, 2020).…”
Section: Mbis For Older Adultsmentioning
confidence: 56%
“…If the pattern of results herein is reproduced, the current study has some clinical implications. First, meditation-and mindfulnessbased interventions have increasingly shown promise to enhance sustained attention, WM, spatial attention, and related cognitive function markers [118][119][120], or protect against their worsening decline across long durations in highly stressful situations…”
Section: Discussionmentioning
confidence: 99%